PENILE CANCER: A STUDY OF 9 CASES AT HASAN SADIKIN HOSPITAL BANDUNG BETWEEN JANUARY 2010 AND DECEMBER 2015 - Firmansyah, Irfan; Safriadi, Ferry (Indonesian Urological Association, 2019)
Objective: Penile cancer are the rarest carcinoma of the genitourinary system that are often devastating for the patient and frequently diagnostically and therapeutically challenging for the Urologist. In view of this, it would be interesting to study the incidence, demographics, presentation, and treatment of the patients. The aim of this study was to report the status of penile cancer at Hasan Sadikin Hospital Bandung. Material & Methods: This was a retrospective study of 9 patients. We study the incidence, demographics, presentation, and treatment of the patients at Hasan Sadikin Hospital Bandung between January 2010 and December 2015. Results: The mean age of the patients was 50.44 ± 12.09 years old. All patients had squamous cell carcinoma. Five patients underwent partial penectomy, 4 patients underwent total penectomy and perineostomy for urinary diversion. Four patients had lymph node localization. A Superficial lymph node dissection was performed in two patients. One of our patient was referred to hemato-oncologist for chemotherapy. Conclusion: Penile cancer seems rare in our hospital. General public should be educated about genital hygiene and early circumcision in male infant as a prophylactic measure. An understanding of the various operative procedures for treatment of the primary tumor and regional lymph nodes is therefore critical in the successful management of this condition.